O rito (fúnebre) individual do neurótico em tempos de dessocialização da morte e do luto: uma leitura psicanalítica das tatuagens in memoriam - Pinho, Miriam Ximenes (2015)
For centuries, the death was treated as a social and public event taking place accompanied by sacred rites. Right after the World War I, a precipitation of the dismantling of the traditional models of care for the dying and the bereaved just occurred. Death has become taboo and that same ban hit everything that it refers, including the mourning that has become an intimate and lonely experience. The desecration of death led to unritualized mourning, however, this did not imply neglect or abandonment of the Dead. Instead, we observe the emergence of new forms of relationship with the Dead in which the rites appear reconfigured, the manner of a bricolage. In order to study these new configurations we have chosen to investigate one of them that is called "in loving memory tattoos" produced due to a bereavement. This research suggests that in loving memory tattoos constitute an neurotic s individual (funeral) rite , that is, a private way of ritualizing mourning and paying funeral tribute in times of suppression of the death of social spaces and unritualized mourning. As we consider the making of a memorial tattoo a private rite, it was important to investigate the function of this rite that can both serve as a possible treatment of the real by the symbolic order in a kind of mourning written on the skin, as a rite that it aims to prolong the relationship with the departed one, producing an endless mourning in which the writing of the mourning never ends